Expression of Fas Ligand by Hepatic Macrophages in Patients with Fulminant Hepatic Failure - Mita, Atsuyoshi; Hashikura, Yasuhiko; Tagawa, Yoh-ichi; Nakayama, Jun; Kawakubo, Masatomo; Miyagawa, Shin-ichi (The American journal of gastroenterology, 2005)
The mechanisms of Fas-Fas ligand (Fas-FasL)-mediated apoptosis in the pathogenesis of fulminant hepatic failure (FHF) have not been well defined. This clinical study was carried out to assess which cells expressed Fas-FasL and to determine their involvement. The subjects were 24 patients with FHF who underwent liver transplantation at our institution. For comparison, nine chronic hepatitis (CH) patients and six living liver donors (LD) were also enrolled. Liver tissues were obtained for histological (hematoxylin-eosin, terminal deoxynucleotidyl transferase [TdT]-mediated dUTP-biotin nick-end labeling [TUNEL], immunohistochemistry, and double immunofluorescence staining) and reverse transcription PCR (RT-PCR; cytokines and chemokines) analysis. The numbers of TUNEL-, FasL-, and CD68-positive cells in the livers of patients with FHF were significantly larger than in those with CH or with normal livers. Double immunofluorescence staining showed that FasL was expressed predominantly on liver macrophages and rarely on CD8-positive lymphocytes. RT-PCR study showed increased expression of FasL; interferon-gamma; interleukin-18; macrophage inhibitory protein-1beta; and regulated upon activation, normal T cell expressed and secreted in the livers of patients with FHF compared with those of LD. Macrophages and their expression of FasL may play roles in the pathogenesis of FHF.